2009
DOI: 10.1016/j.enpol.2009.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Environment Kuznets curve for CO2 emissions: A cointegration analysis for China

Abstract: This study examines the long-run relationship between carbon emissions and energy consumption, income and foreign trade in the case of China by employing time series data of 1975-2005. In particular the study aims at testing whether environmental Kuznets curve (EKC) relationship between CO2 emissions and per capita real GDP holds in the long run or not. Auto regressive distributed lag (ARDL) methodology is employed for empirical analysis. A quadratic relationship between income and CO2 emission has been found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

69
415
3
19

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,042 publications
(540 citation statements)
references
References 47 publications
(63 reference statements)
69
415
3
19
Order By: Relevance
“…In addition, the panel Granger causality analysis revealed bidirectional long-run causalities running: from land urbanization to economic growth and CO 2 emissions; and from economic growth to emissions. The heterogeneous panel Granger causality testing further verified the existence of unidirectional short-term causalities running from economic growth to urbanization and from urbanization (or economic growth) to CO 2 emissions in China, which are in agreement with previous studies (Jalil and Mahmud, 2009;Wang et al, 2011). At the regional scale, there exist only unidirectional short-term causal nexus running from land urbanization to CO 2 emissions and from economic growth to emissions in the eastern and central regions.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In addition, the panel Granger causality analysis revealed bidirectional long-run causalities running: from land urbanization to economic growth and CO 2 emissions; and from economic growth to emissions. The heterogeneous panel Granger causality testing further verified the existence of unidirectional short-term causalities running from economic growth to urbanization and from urbanization (or economic growth) to CO 2 emissions in China, which are in agreement with previous studies (Jalil and Mahmud, 2009;Wang et al, 2011). At the regional scale, there exist only unidirectional short-term causal nexus running from land urbanization to CO 2 emissions and from economic growth to emissions in the eastern and central regions.…”
Section: Discussionsupporting
confidence: 79%
“…previous studies (Wang et al, 2011;Wang et al, 2012a;Du et al, 2012). In addition to the differences as summarized in Table 10, a major difference is that the models we employed are different from those used by Jalil and Mahmud (2009), which may have an impact on the validity of EKC hypothesis. The quadratic model in the regression equations was used in the study by Jalil and Mahmud (2009).…”
Section: Validation Of the Ekc Hypothesis In Chinamentioning
confidence: 99%
See 2 more Smart Citations
“…Using error-correction-based Granger causality models, Acaravci and Ozturk (2010) found a one-way causal relationship to exist between economic growth and energy consumption. The same result was arrived at by Jalil and Mahmud (2009) in their study of China. Results of the study taken by Pao and Tsai (2010) indicated bidirectional strong causality between energy consumption-emissions, and bidirectional long-run causality between energy consumption-output, along with unidirectional causalities between emissions-output and energy consumptionoutput (both strong and short-run, respectively.).…”
Section: Introductionsupporting
confidence: 79%